If you are given y = (-3/7)x - 2 and you want it in the form Ax+By = C, then...
y = (-3/7)x-2
7*y = 7*( (-3/7)x-2) ... multiply both sides by 7
7y = -3x-14 ... distribute and multiply
7y+3x = -3x-14+3x ... add 3x to both sides
3x+7y = -14
The standard form equation is 3x+7y = -14
Answer:
(8,5)
Step-by-step explanation:
5x-2y=30
lets substitute "8" as x and see where that takes us
5(8)-2y=30
40-2y=30
subtract 40 on both sides
-2y=-10
divide by "-2" on both sides
y=5
(8,5) is your answer
Answer:
w>-5/12
Step-by-step explanation:
w > 1/3 - 3/4 = 4/ 12 - 9/ 12
w> -5/12
1.) <span>the ratio of the note A to middle C = 440.0 / 261.6 = 1.6820 ≈ 1.6818
2.) </span><span>the ratio of the note D to middle C = 293.7 / 261.6 = 1.1227
3.) </span><span>D# = 293.6 x 1.0595 = 311.1
4.) </span><span>the ratio of the frequency of G to C is 1 : 262/392 = 1 : 0.6683 ≈ 3 : 2
5.) </span><span>the ratio of the frequency of E to C = 1 : 262/330 = 1 : 0.7939 ≈ 5 : 4
6.) The </span><span>component in a musical note is referred to as the pitch of a sound is the frequency.</span>
Answer:1.8
Step-by-step explanation: